2023
DOI: 10.1039/d3cc01009k
|View full text |Cite
|
Sign up to set email alerts
|

Biogenetic space-guided synthesis of rearranged terpenoids

Abstract: Biogenetic space-guided synthesis is a tool to design efficient chemical syntheses of complex terpenoids by evaluating their surrounding biogenetic space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 91 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…The structural diversity and bioactivities of rearranged steroids render them attractive targets for synthetic chemists, and many syntheses have been accomplished, by our group and others, as covered in several elegant reviews. , During the course of our work on designing a synthetic blueprint for these molecules, we were intrigued by the question of how they are biosynthesized . It has been shown that considering proposed biosynthesis routes while rationally designing synthetic approaches can be an effective strategy for quickly and easily accessing structurally complex natural products from abundant, inexpensive and commercially available starting materials .…”
Section: Introductionmentioning
confidence: 99%
“…The structural diversity and bioactivities of rearranged steroids render them attractive targets for synthetic chemists, and many syntheses have been accomplished, by our group and others, as covered in several elegant reviews. , During the course of our work on designing a synthetic blueprint for these molecules, we were intrigued by the question of how they are biosynthesized . It has been shown that considering proposed biosynthesis routes while rationally designing synthetic approaches can be an effective strategy for quickly and easily accessing structurally complex natural products from abundant, inexpensive and commercially available starting materials .…”
Section: Introductionmentioning
confidence: 99%
“…These feedstocks are then transformed to the target NPs by harnessing skeletal rearrangement and/or selective C–C bond cleavage to edit the skeleton. 52–54 Additionally, various sp 3 C–H bond functionalization/oxidations 55 are employed to install the desired reactive functionalities onto the skeleton (Scheme 1Ca). 27 Given the limited availability of synthetic methods that allow for the desired chemical transformations in conjunction with the desired chemoselectivity, preparing highly functionalized complex NPs through semi-synthesis presents strategic and methodological challenges.…”
Section: Introductionmentioning
confidence: 99%